2014
DOI: 10.2478/slgr-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

Decision Support System for Blockage Management in Fire Service

Abstract: In this article we present the foundations of a decision support system for blockage management in Fire Service. Blockage refers to the situation when all fire units are out and a new incident occurs. The approach is based on two phases: off-line data preparation and online blockage estimation. The off-line phase consists of methods from data mining and natural language processing and results in semantically coherent information granules. The online phase is about building the probabilistic models that estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In [11], mathematical models are suggested for estimating the probability of ERUs' refusal to service a call due to the employment of forces and means to service another call. The mathematical models can be introduced into the ERU dispatching service with the purpose of early redistribution of forces and means on the territory of the settlement, depending on a change of the operational situation.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In [11], mathematical models are suggested for estimating the probability of ERUs' refusal to service a call due to the employment of forces and means to service another call. The mathematical models can be introduced into the ERU dispatching service with the purpose of early redistribution of forces and means on the territory of the settlement, depending on a change of the operational situation.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…According to the results of the literature review [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], it has been found that the known methods for determining the number of EVs with the purpose of equipping ERUs and redeploying the available forces and means are developed mainly for million-plus cities. Such cities are characterized by a higher population density than other types of settlements, which is why the happening of hazardous events and emergencies on their territories is accompanied by a large number of victims and casualties.…”
Section: Development Of a Predictive Model For Determining The Numbermentioning
confidence: 99%